JISMONIY TARBIYA DARSLARIDA HARAKATLI O‘YINLARDAN FOYDALANISh USULLARI - Alimov, J.A. (SCIENCE and SOCIETY, 2025)
This article aims to help students improve their physical fitness, health, endurance, and overall performance. To develop in students the knowledge and necessary movement skills that will allow them to move freely in various conditions. To develop in students the mental and volitional qualities that will help them in life activities. To interest students in various games and physical exercises, to accustom them to following the regime. To develop in students the necessary knowledge and skills to independently organize and conduct active games and to offer practical recommendations and strategies for developing their sportsmanship.